Implementasi Pengelolaan Keuangan Kabupaten di Era Pandemik (Studi kasus di Kabupaten Tangerang-Banten dan Kabupaten Kepulauan Mentawai-Sumatera Barat) - Kulsum*, Umi; Fauziah, Ainil (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Regional financial management, especially in villages, requires necessary attention from policymakers, village heads, and the government above them. The pandemic is a note and a challenge that needs to be accommodated so the village head can handle and manage finances properly. This study aims to discuss the findings of village financial management in the working area of Tangerang Regency, Banten Province, and Mentawai Islands Regency, West Sumatra Province. This study used a qualitative research method with a survey approach. Research that describes phenomena that occur in the field from data collection using purposive sampling techniques and related essential documents. The findings show that village financial management in each district experiences different challenges but remains consistent in referring to the practice of the applicable laws and regulations. In addition, six aspects serve as a reference for village heads and policymakers, namely 1)resources aspect, 2)environment aspect, 3)bureaucratic structure aspect, 4)disposition aspect, 5)communication aspect, and 6)compliance aspect. The research concludes that policymakers and village heads must strengthen the system for implementing and developing financial potential sources in each village.